Managing Haemophilia for Life: 4th Haemophilia Global Summit. (July 2014) - Astermark, J.; Dolan, G.; Hilberg, T.; Jiménez‐Yuste, V.; Laffan, M.; Lassila, R.; Lobet, S.; Martinoli, C.; Perno, C.‐F.
Summary: The 4th Haemophilia Global Summit was held in Potsdam, Germany, in September 2013 and brought together an international faculty of haemophilia experts and delegates from multidisciplinary backgrounds. The programme was designed by an independent Scientific Steering Committee of haemophilia experts and explored global perspectives in haemophilia care, discussing practical approaches to the optimal management of haemophilia now and in the future. The topics outlined in this supplement were selected by the Scientific Steering Committee for their relevance and potential to influence haemophilia care globally. In this supplement from the meeting, Jan Astermark reviews current understanding of risk factors for the development of inhibitory antibodies and discusses whether this risk can be modulated and minimized. Factors key to the improvement of joint health in people with haemophilia are explored, with Carlo Martinoli and Víctor Jiménez‐Yuste discussing the utility of ultrasound for the early detection of haemophilic arthropathy. Other aspects of care necessary for the prevention and management of joint disease in people with haemophilia are outlined by Thomas Hilberg and Sébastian Lobet, who highlight the therapeutic benefits of physiotherapy and sports therapy. Riitta Lassila and Carlo‐Federico Perno describe current knowledge surrounding the risk of transmission of infectious agents via clotting factor concentrates. Finally, different types of extended half‐life technology are evaluated by Mike Laffan, with a focus on the practicalities and challenges associated with these products.